2013
DOI: 10.1039/c2sm27200h
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal complexation of a macromolecule with a small molecular weight natural polyphenol: implications in modulating polymer functionalities

Abstract: Title: Colloidal complexation of a macromolecule with a small molecular weight natural polyphenol: Implications in modulating polymer functionalitiesDescription: This work reports the use of a small molecular weight compound to alter the functionality of an industrially relevant polymer. Spontaneous interactions of tannic acid with methylcellulose resulted in the formation of colloidal particles which showed striking eff ect on the interfacial properties (enhanced oil-water and air-water interface stabilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 40 publications
(59 reference statements)
2
44
0
Order By: Relevance
“…9 The LbL shell can be further functionalized for a specic biological response. 32 The binding stoichiometry indicated that 33 molecules of TA were bonded to methylcellulose via hydrogen bonding. [20][21][22][23][24] TA belongs to a group of hydrolysable tannins and contains digalloyl ester groups connected to a glucose core which has been shown to be versatile for a variety of industrial 25,26 and food applications.…”
Section: Introductionmentioning
confidence: 99%
“…9 The LbL shell can be further functionalized for a specic biological response. 32 The binding stoichiometry indicated that 33 molecules of TA were bonded to methylcellulose via hydrogen bonding. [20][21][22][23][24] TA belongs to a group of hydrolysable tannins and contains digalloyl ester groups connected to a glucose core which has been shown to be versatile for a variety of industrial 25,26 and food applications.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions that occur spontaneously in aqueous environment can be controlled to obtain colloidal structures ranging from nanoscale complexes to microscale capsules to millimeter scale beads ( Figure ). Hydrophilic cellulose derivative (MC) readily interacts with polyphenols such as epigallocatechin gallate or tannic acid to yield nanoscale colloidal complexes which show improvement in the functional properties (such as foaming and emulsification) of the polymer . In addition, the complexation also imparts new functionalities such as loss of thermoreversible gelation that is characteristics of MC, temperature responsiveness of foamed emulsions prepared in the presence of a high concentration of oil, and enhanced stability against coalescence during freeze‐drying of emulsions containing ultrahigh concentration of dispersed oil phase (94 wt%) that consequently enables quick redispersion of dried emulsions …”
Section: Starting Materials For Fabricating Functional and Engineeredmentioning
confidence: 99%
“…Colloidal structures created based on polymer–polyphenol interactions: A) associative complexes of methylcellulose and epigallocatechin gallate (scale bar = 200 nm); B) colloidal complexes prepared at methylcellulose: tannic acid ratio of 2.5:1 w/w and an MC concentration of 0.1 wt% (scale bar = 200 nm); C) complex coacervation core micelles prepared from gelatin–dextran conjugate and tea polyphenols (scale bar = 200 nm); D) zein–tannic acid complex colloidal particles prepared using antisolvent precipitation (scale bar = 200 nm); E) gelatin–epigallocatechin gallate microcapsules prepared using layer‐by‐layer assembly (scale bar = 5 µm); F) methylcellulose–epigallocatechin gallate bead with a distinct core–shell morphology (scale bar = 1 mm) . G) Photographs showing the macroscopic behavior of temperature dependent sol–gel–sol transition of methylcellulose (2 wt%) on top and loss of thermoreversibility in the case of the corresponding methylcellulose:tannic acid (10: 1 w/w) complexes on the bottom; H) images from hot‐stage microscopy analysis (taken every 10 min over a period of 30 min) showing the effect of temperature on the collapse of foamulsions (prepared at an oil‐volume fraction of 0.5) heated at 65 °C (scale bars = 200 µm); and I) photographs showing the effect of freeze‐drying and redispersion on the appearance of emulsions (20 vol% corn oil stained with Nile red) stabilized by CNCs (0.25 wt%), methylcellulose (0.25 wt%), and tannic acid (0.5 wt%) . All panels are reproduced with permission .…”
Section: Starting Materials For Fabricating Functional and Engineeredmentioning
confidence: 99%
See 1 more Smart Citation
“…It forms monolayers with ferric ions 16,17 and also forms multilayered films with neutral polyamides such as poly(N-vinylpyrrolidone), poly(N-vinyl caprolactam), poly(Nisopropylacrylamide), and poly(2-alkyloxazoline) 18−22 by hydrogen bond interactions. These multilayered films are useful for living-cell coating to maintain high viability, possibly because of its low toxicity and appropriate permeability of nutrients or inducer molecules.…”
Section: Introductionmentioning
confidence: 99%